2021
DOI: 10.1001/jamanetworkopen.2021.9444
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Prostate-Specific Antigen Testing Rates and Prostate Cancer Treatments and Outcomes in a National 20-Year Cohort

Abstract: IMPORTANCEThe diagnostic activity for prostate cancer has increased during the past decades.However, the benefit and harm of the increased diagnostic activity have not been quantified in detail for a country or a large region.OBJECTIVE The aim of this study was to evaluate and quantify the association between increases in diagnostic activity driven by prostate-specific antigen testing and incidence of prostate cancer diagnosis, treatment, and mortality. DESIGN, SETTING, AND PARTICIPANTSThis cohort study used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We applied PRISM-PC to estimate the lifetime risk of a prostate cancer diagnosis under three different levels of diagnostic activity and life expectancy. Our PRISM-PC model has been described in detail previously [ 8 , 11 ]. For a hypothetical birth cohort, the model simulates life trajectories from age 40 to age 100 for each man in the cohort.…”
Section: Methodsmentioning
confidence: 99%
“…We applied PRISM-PC to estimate the lifetime risk of a prostate cancer diagnosis under three different levels of diagnostic activity and life expectancy. Our PRISM-PC model has been described in detail previously [ 8 , 11 ]. For a hypothetical birth cohort, the model simulates life trajectories from age 40 to age 100 for each man in the cohort.…”
Section: Methodsmentioning
confidence: 99%
“…16 However, the impact of treating screen-detected low-grade tumors on the overall quality of life for men has been a point of contention in recent studies. 17,18 A diagnosis of prostate cancer also raises significant psychological distress, with several studies reporting minimum to severe anxiety associated with the PSA test. 19 Nevertheless, a follow-up test to confirm the diagnosis of prostate cancer further creates a cycle of anxiety and depression that affects the individual's day-to-day life.…”
Section: Dilemma Of Prostate Cancer Screening For Early Detectionmentioning
confidence: 99%
“…The correlation between elevated serum PSA levels and the possibility of finding a tumor with prostate biopsy has marked the modern age of prostate cancer diagnosis, which, unfortunately, has come with consequences such as incontinence and sexual dysfunction 16 . However, the impact of treating screen‐detected low‐grade tumors on the overall quality of life for men has been a point of contention in recent studies 17,18 . A diagnosis of prostate cancer also raises significant psychological distress, with several studies reporting minimum to severe anxiety associated with the PSA test 19 .…”
Section: Dilemma Of Prostate Cancer Screening For Early Detectionmentioning
confidence: 99%
“…For the first time in 1980, Papsidero et al quantified PSA levels in human blood, signaling the clinical application of PSA, which has since become a common screening tool for PCa today ( 8 10 ). Bergengren et al revealed that using PSA testing resulted in a 15% decrease in prostate cancer deaths from 1996 to 2016 ( 11 ) and it is crucial to clarify the factors that affect PSA in order to ensure quality screening and prevent missed diagnoses. According to recent studies, a higher level of folate may reduce PSA levels and sugar consumption is positively and independently linked to PSA levels in adult American males without prostate cancer ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%